BEYOND GROWTH: SHIFTING THE PARADIGM BY EMBRACING MATURITY (Glocalism: Journal of Culture, Politics and Innovation, 2024)
For many years in the twentieth century, economic growth was synonymous with progress. In the twenty-first century, growth still holds a central place in the concept of development in Western societies, despite being identified as a fetish or an ideology, and its limits having been recognised for decades. Most recently, new debates on the need to develop a paradigm not exclusively based on growth have emerged again in Europe. Scholars have been reflecting on the idea of “beyond growth”, proposing models for new green growth, advocating for degrowth, or suggesting a radical evolution of growth. Next to these perspectives, this contribution suggests that the concept of maturity could successfully shape a new narrative on “beyond growth”. To better describe the idea of maturity, which implies that development is possible without necessarily entailing expansion, two cases are analysed. At the macro level, the U.S. Inflation Reduction Act demonstrates that a new economic approach is possible, featuring bold investments in clean energy. However, the paradigm shift toward a system that does not revolve around growth is not yet in sight in this case. Conversely, at the micro level, the analysed case of some Italian winemakers illustrates what it truly means to value maturity in business activities. Beyond these two cases, further opportunities for alternative development are explored, focusing on digital transformation. It is framed as an opportunity for increased life chances while acknowledging that the same old capitalist logic remains deeply entrenched in it and may jeopardise the opportunities.
Keywords: beyond growth; economic growth; degrowth; green growth; digital revolution